APLIKASI PENGOLAHAN DATA KULIAH KERJA NYATA (KUKERTA) DI PUSAT PENGABDIAN PADA MASYARAKAT (PPM) IAIN SULTHAN TAHA SAIFUDDIN JAMBI - Novhirtamely Kahar (JURNAL AKADEMIKA)
Field Work Experience is a student activity conducted scientifically, systematically placing residents and family as a central point of development, and sustainable. Data processing Field Work Experience in IAIN Sulthan Taha Saifuddin Jambi has not been using the database, so the frequent errors and delays. This study aims to establish a system of data processing applications Field Work Experience at the Public Service Center IAIN Sulthan Taha Saifuddin of Jambi. The system is built using Delphi 7 Programming Language and Microsoft Access 2007 as Database. Data input is the data lecturer, faculty, students, groups, and locations Field Work Experience. The input data will be processed in the registration process, the small groups, shelters, and assessment Field Work Experience. While the output of participant data reports, post, and the value of student kukerta IAIN Sulthan Taha Saifuddin of Jambi . The results showed that with the application system, the data processing kukerta become easier, faster, and data recording errors can be avoided, so that the process of submitting reports to the Head of Public Service Center IAIN Sulthan Taha Saifuddin of Jambi can be according to a set schedule.